The Seepage Evolution Mechanism of Variable Mass of Broken Rock in Karst Collapse Column under the Influence of Mining Stress - Li Xiao-Lei; Li Xin-Lei; Wang Yue; Peng Wei-Hang; Fan Xuan; Cao Zheng-Zheng; Liu Rui-Fu (Geofluids)
When the collapse column of overburden is disturbed by the working face, the grain loss in the karst collapse column occurs by the dissolution and corrosion of groundwater, thereby inducing the water inrush disaster. The test samples are prepared based on the fractal theory and the Talbol grading theory, and the seepage evolution law of fractured rock in collapse column under triaxial stress is studied, by employing the triaxial seepage test equipment. Besides, the seepage mechanics model of broken rock is established and calculated in the COMSOL Multiphysics, and the water-conducting channel under mass loss condition in the collapse column is further elucidated. The research results indicate that the loss ratio of mass is inversely proportional to the Talbol power index, and grain mass loss rate increases with the decrease of the Talbol power index. During the infiltration process, the evolution of pore structure is related with grain size distribution. With the increase of the Talbol power index, the overall porosity increases. Grain loss is an internal factor in seepage loss stability. Flow speed is accelerating, and seepage pathways are communicated with each other to induce the water inrush disaster.